2008
DOI: 10.1186/1472-6963-8-206
|View full text |Cite
|
Sign up to set email alerts
|

Family caregiver quality of life in multiple sclerosis among Kuwaitis: a controlled study

Abstract: BackgroundResearch interest in the quality of life (QOL) of persons with multiple sclerosis (MS) has been spurred by the need to broaden outcome measures. Far less of this interest has been directed at the family caregivers, who bear most of the burden of care. The objectives of the study were: First, to compare the subjective QOL of family caregivers of persons with relapsing remitting and progressive MS, with those of a matched general population sample and caregivers of diabetes and psychiatric patients. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…Two main themes emerged from the interpretations of the text: a silent struggle (I) and imprisoned and invisible (II). According to previous research, this study do confirms findings from the doctoral thesis of Søderlund [7], Manesh and Abedi [6], Alshubali et al [21], Knight et al [20], Buhse [23], as well as Vialtiano et al [24], which increases the validity in this current study.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Two main themes emerged from the interpretations of the text: a silent struggle (I) and imprisoned and invisible (II). According to previous research, this study do confirms findings from the doctoral thesis of Søderlund [7], Manesh and Abedi [6], Alshubali et al [21], Knight et al [20], Buhse [23], as well as Vialtiano et al [24], which increases the validity in this current study.…”
Section: Resultssupporting
confidence: 91%
“…Partners of individuals with MS experienced unpredictability and uncertainty. Alshubali et al [21] found that caregivers to family members suffering from MS are vulnerable and in need of specific attention. Despite this, family caregivers felt that health care personnel did not really understood their daily struggle according to Söderlund [7] and Sälström [22].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the above findings, Asmahan F Alshubaili and Jude U Ohaeri observed in their study that lower education was associated with lower QOL score. 9 Daniel Fu Keung Wong observed that caregivers with lower educational status had more difficulties and lower score of QOL.…”
Section: Qol According To Educational Levelmentioning
confidence: 99%
“…Little research on caregivers of people with MS from other cultures has been conducted. 27,54 However, it is necessary, given the differences in cultural values, caregiving practices, and the availability of rehabilitation services within healthcare systems. For instance, adult day care, residential care, and respite services are limited in Latin America, although it is less costly to hire a full-time personal aide in these countries than in the United States.…”
mentioning
confidence: 99%
“…24 Economic consequences of the condition may include decreased employment 25 and elevated hospital and medical costs. 26 Psychosocial outcomes often include reduced quality of life 27 as well as social anxiety, isolation, 28 and substance abuse. 29 Finally, emotional changes associated with MS include depression 30 and anxiety.…”
mentioning
confidence: 99%